2003
DOI: 10.1016/s0047-6374(03)00037-x
|View full text |Cite
|
Sign up to set email alerts
|

HLA haplotypes and TNF polymorphism do not associate with longevity in the Irish

Abstract: Polymorphism of the human leukocyte antigen has been implicated in a number of autoimmune disorders including ageing. In the course of the present study, no association of the human leukocyte antigen (HLA)-A1, B8, DR3 haplotype with a male Irish aged population, as previously reported, was observed. Two polymorphic nucleotides in the TNF cluster (G(/308A TNF-a and G'/252A TNF-b), associated with increased TNF-a production, were shown to be in tight linkage disequilibrium with the class I and II HLA loci, gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…However, a striking decrease was observed when the aged women (13.1%) were compared to the control women (17.8%). 28 A pivotal role in the innate immune response is also played by NK cells in successful aging. In particular, some studies have showed that decreased NK cell function is associated with an increased incidence of infectious diseases both in aged humans 29 and in mice, 30 highlighting the importance of a well-preserved NK cell function in old age.…”
Section: Listi`et Almentioning
confidence: 99%
“…However, a striking decrease was observed when the aged women (13.1%) were compared to the control women (17.8%). 28 A pivotal role in the innate immune response is also played by NK cells in successful aging. In particular, some studies have showed that decreased NK cell function is associated with an increased incidence of infectious diseases both in aged humans 29 and in mice, 30 highlighting the importance of a well-preserved NK cell function in old age.…”
Section: Listi`et Almentioning
confidence: 99%
“…In nonagenarians/centenarians from Ireland Finland and Japan mtDNA haplogroups and longevity are also associated (Niemi et al, 1998;Tanaka et al, 1998;De Benedictis et al, 1999;Ross et al, 2001;Salvioli et al, 2006a) Interesting conclusions emerge from a comprehensive/critical analysis of the available data on the genetics of centenarians Capri et al, 2006;Salvioli et al, 2006a;Christensen at al., 2006;Candore et al, 2006a): In most of the cases we cannot decide which of the two alternatives is true, but in any case these considerations are crucial as regards replication studies, that is studies that aim to confirm in another population the associations between genetic loci and traits found in one population.…”
Section: The Genetics Of Human Longevity and The Results Of Associatimentioning
confidence: 99%
“…A series of experimental evidence have been published suggesting that some mtDNA haplogroups are associated with longevity (Tanaka et al 1998;De Benedictis et al 1999;Ross et al 2001;Niemi et al 2003), as well as with mitochondrial diseases (Torroni et al 1997;Reynier et al 1999), and complex diseases (Wallace 2005). In particular, in northern Italians, Irish and Finnish, haplogroup J is over-represented in long-living people and centenarians (De Benedictis 1999;Ross et al 2001;Niemi et al 2003), suggesting a role for this mtDNA variant in longevity (Santoro et al 2006).…”
Section: Introductionmentioning
confidence: 99%